The passing of Protestant England : secularisation and social change, c.1920-1960 - Green, S. J. D. (Simon J. D.) (Cambridge ; New York : Cambridge University Press, 2011)
"In The Passing of Protestant England, S.J.D. Green offers an important new account of the causes, courses and consequences of the secularisation of English society. He argues that the critical cultural transformation of modern English society was forged in the agonised abandonment of a long-domesticated Protestant, Christian tradition between 1920 and 1960. Its effects were felt across the nation and amongst all classes. Yet their significance in the evolution of contemporary indigenous identities remains curiously neglected in most mainstream accounts of post-Victorian Britain. Dr Green traces the decline of English ecclesiastical institutions after 1918. He also investigates the eclipse of once-common moral sensibilities during the years up to 1945. Finally, he examines why subsequent efforts to reverse these trends so comprehensively failed. His work will be of enduring interest to modern historians, sociologists of religion, and all those concerned with the future of faith in Britain and beyond"--
Outline of the problem. Towards a social history of religion in modern Britain : secularisation theory, religious change and the fate of Protestant England -- Religion in the twilight zone : a narrative of religious decline and religious change in Britain, c.1920-1960 -- Disclosures of decline. The "soul of England" in an "age of disintegration" : Dean Inge and the "trial of the churches" in the wake of World War I -- The strange death of Puritan England -- Social science and the discovery of a "post-Protestant people" : Rowntree's surveys of York and their other legacy -- Resistance, revival and resignation. The 1944 Education Act : a church-state perspective -- Was there an English religious revival in the 1950s? -- Slouching towards a secular society : expert analysis and lay opinion in the early 1960s -- Conclusion : the passing of Protestant England.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650, 651
Keywords: Great Britain -- Church history -- 20th century; Great Britain -- Religious life and customs -- History -- 20th century; Protestantism -- Great Britain -- History -- 20th century; Religious institutions -- Great Britain -- History -- 20th century; Secularism -- Great Britain -- History -- 20th century; Secularization (Theology); HISTORY -- Europe -- Great Britain; Protestantism; Religious institutions; Secularism; Secularization (Theology); Great Britain; 1900-1999; Electronic books; Church history; History